Vehicle emissions-exposure alters expression of systemic and tissue-specific components of the renin-angiotensin system and promotes outcomes associated with cardiovascular disease and obesity in wild-type C57BL/6 male mice. (2021) - Phipps, Benjamin L.; Suwannasual, Usa; Lucero, JoAnn; Mitchell, Nicholas A.; Lund, Amie K.
Graphical abstract: Highlights: Vehicle emission-exposure increases systemic and adipose renin-angiotensin signaling. Emission-exposure promotes renal, vascular, and adipocyte AT1 receptor expression. Diet and emission-exposure are associated with adipocyte hypertrophy and weight gain. Emission-exposure promotes expression of adipokines and adipose inflammatory factors. High-fat diet promotes an obese adipose phenotype, exacerbated by emission-exposure. Abstract: Exposure to air pollution from traffic-generated sources is known to contribute to the etiology of inflammatory diseases, including cardiovascular disease (CVD) and obesity; however, the signaling pathways involved are still under investigation. Dysregulation of the renin-angiotensin system (RAS) can contribute to CVD and alter lipid storage and inflammation in adipose tissue. Our previous exposure studies revealed that traffic-generated emissions increase RAS signaling, further exacerbated by a high-fat diet. Thus, we investigated the hypothesis that exposure to engine emissions increases systemic and local adipocyte RAS signaling, promoting the expression of factors involved in CVD and obesity. Male C57BL/6 mice (6–8 wk old) were fed either a high-fat (HF, n = 16) or low-fat (LF, n = 16) diet, beginning 30d prior to exposures, and then exposed via inhalation to either filtered air (FA, controls) or a mixture of diesel engine + gasoline engine vehicle emissions (MVE: 100 μg PM/m 3 ) via whole-body inhalation for 6 h/d, 7 d/wk, 30d. Endpoints were assessed via immunofluorescence and RT-qPCR. MVE-exposure promoted vascular adhesion factors (VCAM-1, ICAM-1) expression, monocyte/macrophage sequestration, and oxidative stress in the vasculature, associated with increased angiotensin II receptor type 1 (AT1) expression. In the kidney, MVE-exposure promoted the expression of renin, AT1, and AT2 receptors. In adipose tissue, both HF-diet and MVE-exposure mediated increased epididymal fat pad weight and adipocyte hypertrophy, associated with increased angiotensinogen and AT1 receptor expression; however, these outcomes were further exacerbated in the MVE + HF group. MVE-exposure also induced inflammation, monocyte chemoattractant protein (MCP)-1, and leptin, while reducing insulin receptor and glucose transporter, GLUT4, expression in adipose tissue. Our results indicate that MVE-exposure promotes systemic and local adipose RAS signaling, associated with increased expression of factors contributing to CVD and obesity, further exacerbated by HF diet consumption.